Monitoring the Future: A Continuing Study of American Youth, 2005 (Restricted-Use) - Miech, Richard A. ([Verlag nicht ermittelbar], 2017)
This data collection is part of the Monitoring the Future series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth in eighth, tenth, and twelfth grades. The collection provides two datasets for each year since 1976 that are accessible only through the ICPSR Virtual Data Enclave VDE) and include original variables, including the unaltered weight variable, that in the public-use data were altered or omitted: one dataset without State, County, and Zip Code and one dataset including State, County, and Zip Code. Use of the geographic identifiers such as state, county, or zip code is limited and researchers interested in these variables are encouraged to read FAQs: About MTF Restricted-Use Geographic and Other Variables. Also included as part of each annual collection is a zip archive of the Monitoring the Future public-use data and documentation for each respective year. The basic research design used by the Monitoring the Future study involves annual data collections from eighth, tenth, and twelfth graders throughout the coterminous United States during the spring of each year. The 8th/10th grade surveys used four different questionnaire forms (and only two forms from 1991-1996) rather than the six used with seniors. Identical forms are used for both eighth and tenth grades, and for the most part, questionnaire content is drawn from the twelfth-grade questionnaires. Thus, key demographic variables and measures of drug use and related attitudes and beliefs are generally identical for all three grades. However, many fewer questions about lifestyles and values are included in the 8th/10th grade forms. Drugs covered by this survey include tobacco, smokeless tobacco, alcohol, marijuana, hashish, prescription medications, over-the-counter medications, inhalants, steroids, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), Quaaludes (methaqualone), barbiturates (tranquilizers), cocaine, crack cocaine, ecstasy, methamphetamine, heroin, and GHB (gamma hydroxy butyrate). Other topics include attitudes toward religion, changing roles for women, educational aspirations, self-esteem, exposure to drug education, and violence and crime (both in and out of school).